Sobre o termo neutro: uma análise terminológica conceitual e histórica para o Ensino de Ciências - Carriello, Giovanni Miraveti (Universidade Federal de São Carlos, 2025)
The term neutral and related terms such as neutralize and neutralization are widely used in the contexts of Physics and Chemistry education. Being polysemic, they do not have a single, clear meaning, which often leads to misunderstandings and communication issues. Aiming to address this problem, this study analyzed their use in Brazilian textbooks, dictionaries, and original scientific papers. The research adopts a socio-historical and descriptive terminological approach, based on the Communicative Theory of Terminology, with steps that include organizing a corpus of usage contexts, developing conceptual maps, and creating detailed terminological records that compile uses and definitions of the term and its related concepts. The results highlight the plurality and ambiguity in the use of the terms under study, reflecting a significant historical evolution that tends to directly impact students’ conceptual understanding. The observed diversity and variability demonstrate that the term neutral takes on different meanings depending on the scientific context, ranging from electrical properties in subatomic particles to acid-base characteristics of solutions. The analysis also shows that terminological and conceptual variations can contribute to misunderstandings and alternative conceptions among students, emphasizing the need for greater rigor and clarity in scientific and pedagogical communication. Finally, this study proposes didactic-terminological strategies for managing conceptual ambiguities, aiming to promote a more effective and coherent understanding of scientific concepts taught in schools.
On the neutral term: a conceptual and historical terminological analysis for Science Teaching
Keywords: Terminologia; Conceitos científicos; Neutro; Ensino de Ciências; História da Ciência; Terminology; Scientific concepts; Neutral; Science Education; History of Science; CIENCIAS HUMANAS::EDUCACAO